The (a- b- c)2formula is supplied to discover the squareof the difference in between the 3 numbers without in reality calculating the entirety square and in factorization.(a- b- c)2formula is just one of the significant algebraic identities.To derive the growth of (a- b- c)2formula we simply multiply(a - b - c) by itself to get(a - b - c)2. Let united state learn more about the (a- b- c)2 formula in addition to solved examples.

You are watching: A+b+c squared ## What Is(a- b- c)2 Formula?

We simply read that by multiplying(a - b - c) by itself us can quickly derive the(a - b - c)2formula. Let us see the growth of(a- b- c)2formula.(a- b- c)2=(a - b - c)(a - b - c)(a- b- c)2= a2- abdominal - ac - ab + b2+ bc - ca + bc + c2(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca(a- b- c)2= a2+ b2+ c2- 2(ab - bc + ca)

Let united state see exactly how to use the (a- b- c)2formulain the following section.

Use our totally free online calculator come solve complicated questions. Through stclairdrake.net, discover solutions in simple and straightforward steps.

## Examples on(a- b- c)2 Formula

Let us take a look at a couple of examples to far better understand the formula of(a- b- c)2.

Example 1:Find the value of (a- b- c)2if a = 2,b = 4, and also c = 3using(a - b - c)2formula.

Solution:

To find: (a- b- c)2Given that:a = 2, b = 4, c = 3Using the(a - b - c)2formula,(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca(a- b- c)2= 22 + 42+ 32 - 2(2)(4) +2(4)(3) - 2(3)(2)(a- b- c)2= 4 + 16 + 9 - 16 + 24 - 12

Example 2:Find the worth of (a- b- c)2if a = 12,b = 4, and also c = 5using(a - b - c)2formula.

Solution:

To find: (a- b- c)2Given that:a = 12, b = 4, c = 5Using the(a - b - c)2formula,(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca(a- b- c)2= 122 + 42+ 52 - 2(12)(4) +2(4)(5) - 2(5)(12)(a- b- c)2= 144 + 16 + 25 - 96 + 40 - 120 = 9

Example 3:Find the value of a2+ b2+ c2if (ab - bc + ca) = 10 and (a - b - c) = 20 using(a - b - c)2formula.

Solution:

To find: a2+ b2+ c2Given that:(ab-bc+ca) = 10 and (a - b - c) = 20Using the(a - b - c)2formula,(a- b- c)2= a2+ b2+ c2- 2(ab - bc + ca)(20)2= a2+ b2+ c2- 2(10)400 =a2+ b2+ c2- 20a2+ b2+ c2= 400 + 20 = 420

## FAQs on(a -b - c)2Formulas

### What Is the development of (a -b - c)2Formula?

(a -b - c)2formula is check out as a minusb minus c entirety square. Its development is to express as(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca.

### What Is thea2- b2- c2Formula in Algebra?

The (a - b - c)2formula is just one of the importantalgebraic identities. It is check out as a minus b minusc totality square. The (a - b - c)2formula is expressed as(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca.

### How To simplify Numbers Usingthe(a - b - c)2Formula?

Let us recognize the usage of the (a - b - c)2formula v the assist of the adhering to example.Example:Find the value of (2- 5- 3)2 making use of the (a - b - c)2formula.To find:(2- 5- 3)2Let united state assume that a = 2and b = 5 and also c = 3.We will substitute this in the formula of(a - b - c)2.(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca= 22 + 52 + 32 - 2(2*5) + 2(5*3) - 2(3*2)= 4 + 25 + 9 - 2(10) + 2(15) - 2(6)Answer:(2- 5- 3)2= 36

### How To use the(a - b - c)2Formula offer Steps?

The adhering to steps are adhered to while using(a - b - c)2formula.

See more: Why Do Cats Yawn When You Talk To Them ? Do Cats Yawn When Stressed

Firstlyobserve the sample of the numbers even if it is the 3 numbers have ^2 together wholepower or not such as (a - b - c)2.Write down the formula of(a - b - c)2.(a- b- c)2= a2+ b2+ c2- 2ab + 2bc - 2ca.substitute the value ofa, b and also c in the(a - b - c)2formula and also simplify.